P731Classical and alternative activation and metalloproteinase expression occurs in foam cell macrophages in ApoE null mice in the absence of T- and B-lymphocytes. (15th July 2014) - Thomas, AC; Hayes, EH; Tsaousi, A; Di Gregoli, K; Jenkinson, SR; Bevan, LA; Johnson, JL; Newby, AC
Abstract: Purpose: Classical and alternative macrophage activation could play important roles in atherosclerotic plaque progression and rupture, in part by increasing production of proteases, including matrix metalloproteinases (MMPs), which directly destabilize plaques. Lymphocyte-derived cytokines are believed essential for classical and alternative macrophage activation in plaques, although this hypothesis has not been rigorously tested. Methods and Results: We measured the expression of phenotypic markers and MMPs in classically and alternatively activated mouse macrophages in vitro. We then compared mRNA expression levels of these genes in foam cells derived from subcutaneous sponges of high fat fed ApoE knockout and ApoE/Rag-1 double knockout mice. Furthermore, we performed immunohistochemistry in aortic root and brachiocephalic arteries to detect marker and MMP protein expression in vivo. Classical activation of mouse macrophages in vitro (n=3-6) significantly increased NOS-2, COX-2 and MMPs-13 and -14, whereas alternative activation increased arginase-1, CD206, Ym-1 and MMP-19 expressions (p<0.05). Interestingly, LPS partially reversed the effect of IL-4 on Arg-1 and Ym-1 and completely reversed the overexpression of CD206, so that a combination of LPS and IL-4 generated a combined phenotype with markers of both classically and alternatively activated macrophages. Foam cells in subcutaneous sponges from ApoE mice also expressed phenotypic markers and MMPs, irrespective of Rag-1 genotype. The proportion of plaque staining for markers of classical or alternative activation were examined using immunohistochemistry in brachiocephalic arteries from mice that had been given a high-fat diet. Although the plaque size was smaller in male ApoE/Rag1 KO mice, little difference was found in the proportion of macrophages present (ApoE KO 29 ± 4.3% of plaque area (mean ± SEM); ApoE/Rag1 KO 33 ± 4.8%), or the levels of the markers of activation. For example, male mice had similar iNOS (ApoE KO 16 ± 4.3%; ApoE/Rag1 KO 19 ± 5.1%), arginase-1 (ApoE KO 13 ± 4.1%; ApoE/Rag1 KO 15 ± 4.0%) and Ym-1 content (ApoE KO 2.5 ± 0.80%; ApoE/Rag1 KO 8.7 ± 3.5%). These results suggest that half of the foamy macrophages in the plaques bore markers of classical or alternative activation, irrespective of genotype. Conclusions: Classical and alternative macrophage activation in sponge and plaque foam cell macrophages can occur independently of T- and B-lymphocytes.